Comparison of Host Cytokine Response in Piglets Infected With Toxigenic and Non-toxigenic Staphylococcus hyicus - Li, Yan; Gou, Hongchao; Chu, Pinpin; Zhang, Kunli; Jiang, Zhiyong; Cai, Rujian; Song, Shuai; Bian, Zhibiao; Li, Chunling (Frontiers in Veterinary Science, 2021)
Staphylococcus hyicus is the most common causative agent of exudative epidermitis (EE) in piglets. Staphylococcus hyicus can be grouped into toxigenic and non-toxigenic strains based on its ability to cause EE in pigs. However, the inflammatory response of piglets infected with toxigenic and non-toxigenic S. hyicus has not been elucidated. In this study, we evaluated the serum cytokine profile in piglets inoculated with toxigenic and non-toxigenic S. hyicus strains and recorded the clinical signs in piglets. Fifteen piglets were divided into three groups (n = 5) and inoculated with a toxigenic strain (ZC-4), a non-toxigenic strain (CF-1), and PBS (control), respectively. The changes in serum levels of cytokines (interleukin [IL]-1β, IL-4, IL-6, IL-8, IL-10, IL-12, granulocyte-macrophage colony-stimulating factor, interferon-γ, transforming growth factor-β1, and tumor necrosis factor-α) were evaluated using a cytokine array at 6, 24, 48, and 72 h post inoculation. The results showed that piglets infected with the toxigenic strain exhibited more severe clinical signs and higher mortality than those infected with the non-toxigenic strain. The serum levels of pro-inflammatory cytokine IL-1β were significantly increased in toxigenic-and non-toxigenic-strain-infected piglets compared to those in the control group (p < 0.05), while the anti-inflammatory cytokine IL-10 was significantly up-regulated only in toxigenic group than in control group (p < 0.05). These results indicated that piglets infected with toxigenic and non-toxigenic S. hyicus showed differential infection status and inflammatory responses. Both toxigenic- and non-toxigenic- S. hyicus infection could induce a pro-inflammatory reaction in piglets. In addition, the toxigenic strain induced a strong anti-inflammatory response in piglets as indicated by the increased serum level of IL-10, which may be associated with the severe clinical signs and increased mortality and may be the key cytokine response responsible for pathogenic mechanisms of S. hyicus.